2016
DOI: 10.1016/j.bbmt.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Risk Factor Analysis of Osteoporosis in a Large Cohort of Patients with Chronic Graft-versus-Host Disease

Abstract: The NIH Chronic Graft-versus-Host Disease (cGVHD) Consensus Project Ancillary and Supportive Care Guidelines recommend annual assessment of bone mineral density (BMD) to monitor bone health. The study of osteoporosis in patients with cGVHD has been limited to small numbers of patients and the guidelines are based on experiences in other chronic diseases and expert opinion. We hypothesized that the prevalence of osteoporosis is high in a cohort of 258 patients with moderate to severe cGVHD due to prolonged expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
(56 reference statements)
2
11
0
Order By: Relevance
“…Perhaps, this provides an explanation for our finding that “older age” (pubertal) at the time of cGVHD diagnosis was correlated with presence of VCF. Not surprisingly, in our patient cohort, the femoral neck, a site rich in trabecular bone, was the most frequently affected location, consistent with what has been reported in adult patients with cGVHD 4, 12, 33, 36 . Also, corticosteroids have been shown to exert greater effects on trabecular than cortical bone, which could provide another reason for the observed BMD impairment pattern observed in AHSCT recipients on our study and others 13, 37 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Perhaps, this provides an explanation for our finding that “older age” (pubertal) at the time of cGVHD diagnosis was correlated with presence of VCF. Not surprisingly, in our patient cohort, the femoral neck, a site rich in trabecular bone, was the most frequently affected location, consistent with what has been reported in adult patients with cGVHD 4, 12, 33, 36 . Also, corticosteroids have been shown to exert greater effects on trabecular than cortical bone, which could provide another reason for the observed BMD impairment pattern observed in AHSCT recipients on our study and others 13, 37 .…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the use of systemic corticosteroids has been strongly linked to BMD impairment in pediatric AHSCT recipients 4, 10, 15 . When comparing our pediatric versus adult cGVHD cohort (concurrently enrolled on the same study) we observed a higher rate of significant BMD impairment, with DEXA z-score ≤-2 at three sites in 39% of pediatric versus17% of adult patients, despite both groups having a similarly high prevalence of severe cGVHD 33 . Pediatric AHSCT recipients are particularly vulnerable to bone health impairments.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, it is straightforward to understand the presence of a close relationship between hematopoiesis and bone remodeling, considering that several studies found that PLTs, the cytoplasmic fragments derived from megakaryocytes, have a critical role in skeletal homeostasis, modulating bone formation and resorption [ 19 , 20 ]. An increasing number of clinical studies evaluated the relationship between PLTs and OP status based on BMD, considering and comparing healthy, osteopenic, and OP subjects [ 21. , 22.…”
Section: Plt-related Factors As Op Biomarkersmentioning
confidence: 99%
“…GVHD manifestations are similar to those in patients with malignant disorders, and incidence and severity vary according to the graft source, HLA compatibility, and patient age [43]. Depending on its severity, chronic GVHD can negatively affect long-term quality of life and requires monitoring and intervention for control [44,45]. The incidence of malignant disorders after HCT for thalassemia is <10 per 100,000 per year and does not appear to be higher than in patients with β-thalassemia major that are not transplanted [46,47].…”
Section: Hct-related Complicationsmentioning
confidence: 99%